Women in Refugee Law, Policy and Practice: An Introduction to The Refugee Survey Quarterly Special Issue. (27th July 2022) - Dustin, Moira; Querton, Christel
Abstract: As co-founders and conveners of the Women in Refugee Law (WiRL) network, we are delighted to introduce this Special Issue. The contributors are WiRL members who take forward the network's objectives of recentring the study of refugee women by reviewing the state of protection in domestic jurisdictions and internationally, identifying setbacks to adequate protection for women at risk of persecution, and proposing inclusive ways forward.